(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
East Indian Lemongrass, or Cymbopogon flexuosus, is a multipurpose plant that has beenprized for ages due to its many use in medicine and cooking. This fragrant plant may be found in itsnative India and other regions of Asia, and it is highly prized for the essential oils it produces.Cymbopogon flexuosus and its bioactive components have been under intense scrutiny in recent yearsowing to their promising medical and commercial implications. Natural and synthetic antioxidants areboth vital in protecting the body from the damaging effects of free radicals. They protect cells andtissues from damage caused by free radicals, lowering the likelihood of developing cancer,cardiovascular disease, or neurological illness. Because of its high antioxidant content, Cymbopogonflexuosus is a promising newcomer to the world of natural antioxidants. Concurrently, Cymbopogonflexuosus antimicrobial substances have drawn attention for their potential to fight off a wide range ofgerms. These compounds have shown strong antibacterial, antifungal, and antiviral characteristics,making them useful for the treatment of infectious illnesses in the pharmaceutical and agriculturalindustries. In this paper revie the antioxidants and antimicrobial compounds of Cymbopogon flexoususSp. Krishna.